Evaluation of the Health Program at Escola Carioca by the research-action methodology (Brazilian Journal of Health Research, 2022)
Introduction: The health at the national school program, basis for the PSE Carioca, is a strategy of permanent integration and articulation between education and health policies and actions. Objectives: To analyze the contribution of the methodological framework of action research in the evaluation in the Health at School Program. Methods: an evaluative study, with a qualitative approach, which describes a stage in the methodological framework of action research. The data were collected from nine managers of the Programa Saúde na Escola Carioca through an electronic questionnaire, stored in the researchers’ personal electronic device. Results: Most participants stated that in some way the method helped with what corresponds to the monitoring and evaluation component of the Programa Saúde na Escola Carioca. Conclusion: Action research is a valuable and potentially transformative method in the reflection-action of individuals and collectivity. The use of the method was favorable in facing the challenge of intersectorality and resulted in improvements in the practice of monitoring and evaluating the Health at School Program.
Keywords: Nursing; Methodological Research in Nursing; Measures, Methods and Theories; Evaluation of Health Programs and Projects; Evaluation of Health Programs and Projects. School Health Services